Trader types and volatility of emission allowance prices: evidence from EU ETS Phase I - Balietti, Anca (Energy policy, 2016)
This paper studies the relation between the trading activity of market participants and the volatility of the European Emission Allowance price during Phase I of the European Union Emission Trading System (EU ETS). We focus on the contrasting roles of different trader types. We find evidence of a positive and significant trading activity-volatility relation, which appears to be stronger when accounting for trader type. The positive relation can be mainly attributed to energy providers. In contrast, industrial companies seem to have traded more frequently when volatility levels were lower. Finally, the non-liable players, represented by financial intermediaries, appear to have acted as a flexible counterparty, trading more with the energy sector when volatility was higher, and more with the industrial firms when volatility was lower. We discuss possible explanations for these contrasted positions. Understanding the trading activity-volatility link is relevant for evaluating the efficiency of the EU ETS. Although the relation is generally positive, many players remained often inactive and traded mostly when volatility levels were lower. Policies targeting the engagement of less active players could lead to a smoother incorporation of information into prices and to an increase in market efficiency.